The Female Body and the Body Politic in Sex Scenes of Lou Ye’s Film: A Multimodal Discourse Analysis of Summer Palace - Xiaoling Zhan; Norfarizah Mohd Bakhir (Wacana Seni Journal of Arts Discourse, 2024)
This article discusses the body politic of Yu Hong in the postsocialist Chinese film–Summer Palace (2006). Director Lou Ye places Yu Hong’s body in the sex scenes that metaphorically expresses a traumatic and sensitive political event, the “June Fourth Incident.” The portrayal of sexual intercourse, nudity, and this historical event is the unspeakable “secret” in mainland Chinese media. Therefore, the authors raise the question that, when sexual intercourse and the female body enter political discourse, how do we deal with the complex and dynamic power structures behind bodily attributes and the “anachronistic” historical objects that do not fit into the mainstream narrative and epistemological spaces? Drawing on body politic theory, feminist film theory, and a semiotic framework, we adopt multimodal critical discourse analysis to assess power relations and ideologies behind Yu’s body attributes in the sex scenes. The findings indicate that Lou constructs a complex communication system, using her body as a carrier of communication to express self-consciousness, constructing female subjectivity through the writing of feminine discourse, with the political purpose of seeking the freedom of the written word. Sexual liberation is sought by establishing a transgressive body that is not accepted by the mainstream and opposes the inherent power of government. Yu’s bodily pleasure is set up as an expression of narcissistic individualism through love, producing a vision of political ecstasy. Her melancholy body metaphor for the discomfort and confusion that preceded the student movement and the post-traumatic ambivalence. Using the female body as a site of political discourse and sexual liberation offers a new reading strategy for analysing the representation of the female body in film and other forms of media. In making the argument, the study contributes valuable scholarship to the film studies focused on sexual, gender, and political marginalised discourse.